СКЛАД АДМІНІСТРАТИВНОГО ПРОСТУПКУ ЯК ЮРИДИЧНА ПІДСТАВА АДМІНІСТРАТИВНОЇ ВІДПОВІДАЛЬНОСТІ - Панасюк, Оксана Володимирівна (SUPREMANCE OF LAW, 2017)
The concepts and significance of the legal composition of administrative misconduct for administrative -legal science are analyzed, its difference from the general concept of misconduct is characterized. The structure of the administrative misconduct was established and detailed, and a detailed description of each component of the indicated legal category was carried out.
Keywords: misconduct; administrative tort; legal structure; Administrative Code